Plasma lipoprotein and apolipoprotein levels in Taipei and Framingham - Lyu L-C (臺灣營養學會, 2014)
食品保健功能的發現常起源於觀察型流行病學研究(observational epidemiological study)探討族群飲食與疾病現象之相關研究結果。本文以魚、紅酒、茶及黃豆為例，闡述觀察型流行病學文獻與食品保健功能成份，如魚油、植多酚(plant polyphenols)及異黃酮(isofavonoids)的發現之旅。經由生態相關(ecological correlation)，世代追蹤(follow-up cohort)及病例對照(case-control)的研究方法，西方流行病學家分析人類飲食中可能與疾病預防及健康促進相關的食物特殊成份，並嘗試解釋可能的原因及相關機制；如再經由其他實驗設計深入了解生化機轉及臨床的功效，最後可經由介入研究(intervention study)進一步探討於特定族群之效能。觀察型流行病學文獻中描述丹麥的愛斯基摩人吃深海魚、法國人喝紅酒、東方人喝茶及攝取黃豆食品，並顯示這些飲食生活型態與疾病健康可能有密不可分的關係，因而近年來相關之臨床及生化機轉研究正急速增加中。雖然西方營養流行病學相關研究汗牛充棟，針對東方人群者卻仍然稀少。由於現今實證醫學(evidence-based medicine)是國內行政立法機關管理健康食品的主流思想，了解此四種食品之觀察型流行病學研究歷史及營養流行病學方法學之優點及限制，可增進我們對食品保健功能之流行病學相關研究的知識。 Many functional foods are attributed from observational epidemiological studies that examine the relationships between diet and diseases in various human populations. This review focuses on fish, red wine, tea and soy as examples to illustrate the discovery of functional components such as n-3 fatty acids, plant polyphenols and isoflavonoids. Using study designs, such as ecological correlation, follow-up cohort and case-control studies, epidemiologists have been trying to describe and understand the possible relationships between certain food/dietary components and disease prevention/health promotion. We have learned that Greenland Eskimos eat fish from the deep oceans, the French drink red wine, East Asians drink tea and consume soybean products. These dietary practices may be significantly associated with certain health impact and imply potential functional components in diet. Therefore, related laboratory experiments and clinical trials are flourishing. Since the evidence-based medicine paradigm is the main principle in our legalistic and executive ties and limitations of related epidemiological studies. http://www.ceps.com.tw/ec/ecjnlarticleView.aspx?jnlcattype=1&jnlptype=5&jnltype=478&jnliid=447&issueiid=1679&atliid=10653